Marketing tools in assessing the strategic position of a private hockey camp in the sports services market - V.V. Nasonov; D.S. Rechapov (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the competitiveness of a private hockey camp according to the McKinsey model. Methods and structure of the study. The object of the experiment was a private hockey camp "YACH-CAMP". The McKinsey matrix was used to assess the competitive position of a sports organization and the potential of various activities to promote services in new segments. Results and conclusions. The results of assessing the competitive advantage of a private sports camp showed that the greatest importance in its formation is the availability of financial, human, investment resources. The cooperation of the private camp management with sponsors and strategic partners indicates a well-built political strategy, which is an effective marketing tool, as well as evidence of investment attractiveness for many large companies in the region.